ANALISIS DAN PERANCANGAN GALERI FOTO ONLINE PHOTOID BERBASIS WEB - Sigit Birowo, S.Kom., M.Kom (Jurnal Informatika dan Bisnis, 2018)
The purpose of this paper is to make a online web-based photography gallery for the photographer to be able to share each other's work as well as his knowledge through the website this PhotoID. This website is a photo gallery featuring the works of photography by categories photos and has a feature to be able to view the metadata of a photo, coupled with the article and the article information regarding photography contest information and contest photography. Analysis of the system running is to use the analysis is SDLC where the methods of analysis the authors analyze the needs of the user. At the design stage the authors designed the stages used in the manufacture website.The result is the creation of an online photo gallery PhotoID. PhotoID website is a forum for the exchange of photographs by photographers photo. The conclusion is that when using the website PhotoID then the user is given the ease and comfort in visiting photograph photographs by the photographer so that the website can be used by anyone who use itKeywords: photo gallery, bootstrap, photography, code igniter